A New Year, a New You? Heterogeneity and Self-Control in Food Purchases - Laurens Cherchye; Bram De Rock; Rachel Griffith; Martin O'Connell; Kate Smith; Frederic Vermeulen (Institute of Labor Economics (IZA), 2017)
We document considerable within-person (over time) variation in diet quality that is not fully explained by responses to fluctuations in the economic environment. We propose a two-selves model that provides a structural interpretation to this variation, in which food choices are a compromise between a healthy and an unhealthy self, each with well-behaved preferences. We show that the data are consistent with this model using revealed preference methods. The extent of self-control problems is higher among younger and lower income consumers, though this is overstated if we do not control for responses to fluctuations in the economic environment. Our results are intuitively related to stated attitudes on self-control.
Keywords: C14; D12; D90; I12; 330; two-selves model; self-control; revealed preferences